Some Hermite-Hadamard type inequalities for functions whose exponentials are convex - DRAGOMIR, Silvestru Sever; GOMM, Ian (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Some inequalities of Hermite-Hadamard type for functions whose ex- ponentials are convex are obtained. Mathematics Subject Classification (2010): 26D15, 25D10.